2007
DOI: 10.7202/032693ar
|View full text |Cite
|
Sign up to set email alerts
|

Late Holocene Pollen Stratigraphy in Four Northeastern United States Lakes

Abstract: Four pollen diagrams from Maine, New York, and Pennsylvania provide fine resolution (40 or 80 years) records of vegetation change in northeastern United States during the past 2000 years. A long term increase in pollen accumulation rates (PAR) of Picea occurred at the three sites in Maine and New York. Around 1100 years ago, Tsuga and Fagus decreased and Quercus and Castanea increased at Ely Lake in northeastern Pennsylvania. Around 500 years ago, Tsuga and Fagus greatly decreased in Maine and northern New Yor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
7
6
0
Order By: Relevance
“…The two oldest time periods ( ad 1200–1350 and ad 1500–1600) correspond to a high frequency of fire events with a low flux of deposition compared with the ad 1830–1930 time period, which was characterized by less frequent events of high intensity (Savarino and Legrand, 1998). The authors found that their Index of Fire is in fairly good agreement with charcoal records obtained from three sites in Maine (Conroy Lake and Basin Pond) and New York (Clear Pond) by Gajewski (1985), suggesting that Eastern North America is the source of biomass burning material in central Greenland over the last millennium.…”
Section: Ice-core Records Of Changes In Biomass Burningsupporting
confidence: 57%
“…The two oldest time periods ( ad 1200–1350 and ad 1500–1600) correspond to a high frequency of fire events with a low flux of deposition compared with the ad 1830–1930 time period, which was characterized by less frequent events of high intensity (Savarino and Legrand, 1998). The authors found that their Index of Fire is in fairly good agreement with charcoal records obtained from three sites in Maine (Conroy Lake and Basin Pond) and New York (Clear Pond) by Gajewski (1985), suggesting that Eastern North America is the source of biomass burning material in central Greenland over the last millennium.…”
Section: Ice-core Records Of Changes In Biomass Burningsupporting
confidence: 57%
“…Our climatic interpretation of the Wolf-62 diatom series broadly corroborates the Clear Pond pollen record (Gajewski et al, 1987) in that both indicate exceptionally dry conditions in the Adirondacks c. AD 500-1000 followed by mostly wetter conditions to the 18th century (Figure 7c and h). However, the Wolf-62 record puts the end of the initial dry period about a century later than the Clear Pond record, and it suggests that the 'Little Ice Age' (LIA; c. AD 1350-1800; Jones et al, 2001;Maasch et al, 2005) was generally wetter than the MCA rather than similar or somewhat drier as was indicated for Clear Pond.…”
Section: Regional Hydroclimate Historysupporting
confidence: 81%
“…Sediments from the deepest portion of the basin (>21 m) display rhythmic, fundamentally annual layering as reported by Gajewski et al (1987). The brown sediments pre-dating European settlement (assessed by pollen analysis) are finely and very regularly partitioned by thin, darker bands, which presumably represent winter layers.…”
Section: The Study Areasupporting
confidence: 58%
“…Annually laminated lake sediments provide the possibility of investigating magnetic parameters as high-resolution proxies of continental climate change. Lake Ely in northeastern Pennsylvania has deposited annually laminated sediments for at least 2000 yr (Gajewski et al 1987). The lake is located in a tectonically stable region and is far from heavily industrialized areas.…”
Section: Introductionmentioning
confidence: 99%